Lessons From the Frontline: Navigating the Complexities of Qualitative Research, Reflections From Early-Career Researchers - Gerald Mirirai Mabweazara; Tamuka Chekero; Tendai Elvis Mutembedza; Pakhani Mhazo (International Journal of Qualitative Methods)
This paper investigates the complexities of qualitative research through the reflective narratives of four graduate students in the social sciences. Through narrative analysis, this paper highlights the unpredictable and often non-linear dynamics of empirical fieldwork, participant recruitment, and data collection processes. Despite guidance from academic supervisors, existing literature and ethics review boards, novice researchers frequently encounter challenges that diverge from established research models. The findings underscore the necessity for early-career researchers to maintain adaptability in the face of unforeseen obstacles. Drawing from the researchers’ experiences in sociology of health, anthropology, social psychology, and public health, the paper addresses critical issues encountered in sensitive research contexts, such as trust-building, ethical dilemmas, and participant recruitment. We employ Nyamnjoh’s concept of “nimble-footedness,” to offer a framework for navigating the dynamic and often chaotic nature of qualitative inquiry, while emphasising the importance of methodological flexibility and cultural sensitivity. Ultimately, this research argues that the inherent unpredictability of qualitative research enriches the research process, advocating for a transparent approach that embraces the messiness of fieldwork. As social research evolves, fostering resilience and adaptability among emerging researchers is vital for capturing the richness of human experiences within diverse and complex contexts.